Analysis of the impact of augmented reality on learning in times of pandemic - Vera Cuya, Ronald Martín (2023)
21st LACCEI International Multi-Conference for Engineering, Education, and Technology & 4th CLADI-CONFEDI: “Leadership in Education and Innovation in Engineering in the Framework of Global Transformations: Integration and Alliances for Integral Development”, Hybrid Event.